A magnetic negative stiffness eddy-current inertial mass damper for cable vibration mitigation. (1st April 2023) - Wang, Zhi-hao; Cheng, Zhi-peng; Yin, Guang-zhao; Shen, Wenai
Highlights: A novel passive damper is proposed for cable vibration control. A mechanical model of the damper is proposed and validated. The damper outperforms typical passive dampers for cable single-mode and multimode control. Abstract: Previous studies have shown superior control performance in mitigating vibrations of stay cables by using passive control devices such as negative stiffness dampers (NSDs) and inertial mass dampers (IMDs). Integrating the advantages of the two dampers, we propose a novel passive control device termed magnetic negative stiffness eddy-current inertial mass damper (MNS-ECIMD) for cable vibration mitigation. A mechanical model of the MNS-ECIMD is proposed and validated against dynamic test data of a small-scale prototype. A parametric analysis is conducted based on the finite difference model of the cable-damper system to investigate the effects of the magnetic negative stiffness coefficient, inertance coefficient, and eddy-current damping coefficient of the MNS-ECIMD on cable vibration mitigation performance. The MNS-ECIMD performance is further validated using a small-scale cable test, of which the results illustrate its superior performance for the first two modes compared with the ECIMD. A simple parameter optimization procedure is then presented for cable multi-mode vibration control, which is then demonstrated via numerical simulation of a 306 m-long stay cable of Stonecutter Bridge in Hong Kong. Numerical results illustrate that the MNS-ECIMD significantly outperforms conventional viscous dampers and the ECIMD for cable multi-mode vibration control, owing to the additional negative stiffness effect.